Об оценках решений уравнений движения вязкой жидкости в подвижной полости с пористым демпфером - Судаков, С.Н. (Український математичний журнал, 1993)
Estimates for L₂-norms of solutions of equations of motion for viscous fluid in a moving elliptic cavity with a porous damper are obtained.